Secular Jewish Identity and Public Religious Participation within Australian Secular Multiculturalism - Creese, Jennifer (Religions, 2019)
Many Australian Jews label their Jewish identity as secular. However, public representations of Jewish culture within Australian multiculturalism frequently highlight the religious practices of Judaism as markers of Jewish cultural authenticity. This study explores how secular Jews sometimes perform and reference Jewish religious practice when participating in communal events, and when identifying as Jewish to non-Jews in social interactions and in interactions with the state. Ethnographic participant observation and semi-structured in-depth interviews with nine self-identified secular Jews living in Queensland, Australia, were employed to gather data. These self-identified secular Jews within the community incorporate little religiosity in their private lives, yet in public they often identify with religious practice, and use a religious framework when describing and representing Jewishness to outsiders. This suggests that public Jewishness within Queensland multiculturalism might be considered a performative identity, where acts and statements of religious behavior construct and signify Jewish group cultural distinctiveness in mainstream society. These secular Jews, it is suggested, may participate in this performativity in order to partake in the social capital of communal religious institutions, and to maintain a space for Jewish identity in multicultural secular society, so that their individual cultural interpretations of Jewishness might be realised.